RUNX2 facilitates aggressiveness and chemoresistance of triple negative breast cancer cells via activating MMP1 - Si, Wentao; Xu, Xiaodan; Wan, Lijuan; Lv, Fengxu; Wei, Wei; Xu, Xiaojun; Li, Wei; Huang, Dabing; Zhang, Leisheng; Li, Feifei (Frontiers in Oncology, 2022)
Breast cancer remains the most common malignancy in women and constantly threatens the lives of patients worldwide. State-of-the-art renewal has indicated the involvement of RUNX-associated transcription factor 2 (RUNX2) in tumorigenesis and cancer progression, yet the detailed information during breast cancer is largely obscure. Herein, we took advantage of breast cancer cell lines and in vivo tumorigenicity test as well as multifaceted phenotypic analyses (e.g., RNA-sequencing, ChIP and qRT-PCR assay) to verify the pathogenic mechanism of RUNX2 in triple negative breast cancer aggressiveness and chemoresistance. Strikingly, the proliferation, migration, invasion and chemoresistance of resistant cell lines in triple negative breast cancer was effectively suppressed by RUNX2 silencing, and the in vivo tumorigenicity was significantly weakened as well. Furthermore, with the aid of transcriptomic and bioinformatic analyses, we found MMP1 was highly expressed in triple negative breast cancer and showed a strong correlation with the poor prognosis of the patients, which was consistent with the expression pattern of RUNX2. Finally, by conducting ChIP and qRT-PCR assessment, we verified that RUNX2 functioned via directly binding to the specific motifs in the promoter of MMP1 and thus activating the transcriptional process. Collectively, our data demonstrated the facilitating effect of RUNX2 during triple negative breast cancer progression by directly orchestrating the expression of MMP1, which supplies overwhelming new references for RUNX2-MMP1 axis serving as a novel candidate for breast cancer diagnosis and treatment.